1987
DOI: 10.1021/bi00388a049
|View full text |Cite
|
Sign up to set email alerts
|

The binding domain on horse cytochrome c and Rhodobacter sphaeroides cytochrome c2 for the Rhodobacter sphaeroides cytochrome bc1 complex

Abstract: The interaction of the Rhodobacter sphaeroides cytochrome bc1 complex with Rb. sphaeroides cytochrome c2 and horse cytochrome c was studied by using specific lysine modification and ionic strength dependence methods. The rate of the reactions with both cytochrome c and cytochrome c2 decreased rapidly with increasing ionic strength above 0.2 M NaCl. The ionic strength dependence suggested that electrostatic interactions were equally important to the reactions of the two cytochromes, even though they have opposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…5 (43); the second method was a nonlinear fitting of a biexponential function to the SR curves (see “Experimental Procedures” for details). Because the binding between the two redox partners is in part controlled by electrostatic interactions, (2327, 56, 57) the changes in the ionic strength were used to effectively manipulate the binding equilibrium of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…5 (43); the second method was a nonlinear fitting of a biexponential function to the SR curves (see “Experimental Procedures” for details). Because the binding between the two redox partners is in part controlled by electrostatic interactions, (2327, 56, 57) the changes in the ionic strength were used to effectively manipulate the binding equilibrium of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the interaction of Ru-72-Cc and native horse cytochrome c with R. sphaeroides cytochrome bc 1 , steady-state kinetics were carried out under high ionic strength conditions, where previous studies have shown that the Michaelis constant K m is a good measure of the binding interaction (22). Native horse cytochrome c was found to have a V max of 3.8 Ϯ 0.5 M cytochrome c reduced per min/nM cytochrome b and a K m of 10 Ϯ 1 M in buffer containing 25 mM sodium phosphate (pH 7.0), 150 mM NaCl, and 0.3 mM EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of nonenzymatic reduction of cytochrome c by Q 0 C 10 BrH 2 , determined under the same conditions in the absence of enzyme, was subtracted. The steady-state parameters V max and K m were determined from EadieHofstee plots of the initial velocities as described (22).…”
mentioning
confidence: 99%
“…These data, when examined with the integrated Michaelis-Menten equation, yielded a K m in the order of 0.4 µM which is similar to that reported for the reduction of Rba. sphaeroides cytochrome c 2 by mitochrondrial bc 1 complex (Hall et al 1987). Further, the rate of oxygen consumption catalyzed by membrane fragments (30 nM bc 1 complex) with Na-ascorbate plus cytochrome c 551 as donors was determined to test the efficiency of cytochrome c 551 in reducing the terminal oxidase.…”
Section: Respiratory Activities In Membrane Fragmentsmentioning
confidence: 99%